Effect of Self-Microemulsifying Lipid Formulations on the Dissolution and Compaction Profiles of Tablets Containing Theophylline; A BCS Class I Compound - Naser M.Y. Hasan, Mohammad A. Khaleel, Abdullah S. Altwairqi, Abdulmajeed G. Alqurashi, Abduallah H. Altwairqi (Journal of Applied Pharmaceutical Science, 2018)
There is growing interest amongst formulation scientists to use self-emulsifying lipid technology as an approach to improve dissolution and hence absorption of poorly-water soluble drugs. Nonetheless, lipid-based formulations require that oil content is encapsulated in soft gelatin capsules which might exhibit some disadvantages. To overcome these limitations, solid self-micro-emulsifying drug delivery system (S-SMEDDS) is introduced as an alternative approach. The preferred dosage form for BCS class I compounds is tablets yet, some drugs which belong to this category might suffer from enzymatic degradation and gut wall efflux. The effect of converting liquid SMEDDS into compressed tablets containing a BCS class 1 compound is investigated. A SMEDDS oil formulation representing type III A lipid class was converted into S-SMEDDS using solid carrier adsorption method and compressed into tablets containing theophylline. The effect of oil loading factor on compressibility, disintegration and dissolution kinetics of theophylline from various tablet formulation was investigated. Increasing oil content in the compressed tablets ensued in a progressive decrease in the hardness of tablets. Analysis of the dissolution kinetic data for tested theophylline preparations shows that it follows first-order or Higuchi kinetics. Fast dissolving tablet formulations were obtained at including an optimum oil concentration of 5% w/w.
Keywords: SMEDDS, Lipid formulations, Solid SMEDDS, Theophylline, Dissolution.